Virtual Trauma Interventions for the Treatment of Post-traumatic Stress Disorders: A Scoping Review - Knaust, Thiemo; Felnhofer, Anna; Kothgassner, Oswald D.; Höllmer, Helge; Gorzka, Robert-Jacek; Schulz, Holger (Frontiers in Psychology, 2020)
Some post-traumatic stress disorder (PTSD) patients do not benefit from imaginal exposure therapy. One possible approach to reach such patients are virtual trauma interventions. Herein, a qualitative scoping review was conducted. Different types of virtual trauma exposure interventions were identified. For each type of virtual trauma exposure interventions it was examined in detail: (1) which in sensu trauma exposure approach serves as therapeutic framework, how it was transferred into virtual reality, and if it was manualized; (2) which hardware and software were used; (3) whether the influence of spatial and social presence on the efficacy of virtual trauma interventions have been measured, and (4) whether the efficacy of virtual trauma interventions for PTSD patients having imagination difficulties was evaluated. These research questions were analyzed qualitatively. Accordingly, an extensive literature search was conducted using the databases Web of Science, PsycINFO, LIVIVO, PTSDpubs, and PubMed for scientific articles published between January 2013 and July 2020. Only studies aimed to reduce PTSD symptoms using virtual trauma interventions were included. The literature search was not limited to a specific study design, treatment/intervention method, or a minimum sample size. Eighteen studies were identified, which reported three different virtual trauma intervention approaches, namely, virtual reality exposure therapy (VRET), multi-modular motion-assisted memory desensitization and reconsolidation (3MDR), and action-centered exposure therapy (ACET). Seven randomized controlled trials (RCTs), two pilot studies, and one case study were focused on VRET; while two RCTs, one pilot study, and three case studies focused on 3MDR, and two case studies on ACET. Regarding the first research question (1), the results show that VRET is based on prolonged exposure, aiming for a virtual re-creation of the patient's traumatic recounting. Several treatment protocols exist for VRET. 3MDR is based on eye movement desensitization and reprocessing, aiming to reduce the patient's avoidance behavior. In 3MDR patients walk toward individualized trauma-related symbolic images in a cave automatic virtual environment (CAVE). One treatment protocol exists for 3MDR. ACET is based on the inhibitory learning theory, aiming for active interactions with a virtual trauma-associated environment to alter the anxiety structure through new secondary inhibitory learning. One treatment protocol exists for ACET. For the second research question (2), the results indicate that all VRET studies used head-mounted displays (HMDs) with a virtual version of the Iraq/Afghanistan or the World Trade Center attacks, while 3MDR studies utilized two different versions of a CAVE with personalized trauma-related images, and the ACET studies used HMDs with virtual street scenarios. For the third research question (3), the results demonstrate that the influence of spatial or social presence on the efficacy of virtual trauma interventions was not examined in any of the included studies. Similarly, for the fourth research question (4), the results show that empirical evidence for the efficacy of virtual trauma interventions on PTSD patients having imagination difficulties was lacking. Therefore, such empirical studies are needed to fill these research gaps.